Király József esperes-plébános elleni ítélet a Beneš-dekrétumok alapján - PETHEŐ, Attila (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2026)
Judicial Decision against Dean and Parish Priest József Király under the Beneš Decrees. This study analyses the 1946 People’s Court trial of József Király, parish priest of Csicsó (Číčov), within the framework of the Beneš Decrees and Decree No. 33/1945 of the Slovak National Council. Based primarily on the records of the Komárno District People’s Court and supplemented by diocesan and local ecclesiastical sources, the article reconstructs the charges, witness testimonies, judicial reasoning, and verdict in order to assess how post-war retributive legislation was applied to a representative of the Hungarian Catholic clergy in southern Slovakia. Ordained in 1921, Király combined pastoral service with active engagement in Hungarian minority politics. During the First Czechoslovak Republic, he held a leading role in the National Christian Socialist Party at the district level, and from 1939 he served as a member of the Hungarian Parliament. After 1945, these activities became the foundation of accusations that he had contributed to the dismemberment of Czechoslovakia in 1938 and supported the “fascist occupation”. He was further charged with anti-Soviet agitation and collaboration. The court dismissed several concrete allegations for lack of evidence, including participation in secret meetings and direct incitement. Nevertheless, it found Király guilty of collaboration on the basis of his political functions, interpreting them as structural support for the Hungarian regime. On 28 August 1946, he was sentenced to six months’ imprisonment, confiscation of property, and five years’ deprivation of civil rights, with no right of appeal. The case reveals the predominance of political categorization and collective responsibility over individualized assessment. While mitigating factors – such as Király’s documented assistance to persecuted persons and his own arrest by the Arrow Cross regime – were acknowledged, they did not alter the court’s fundamental logic. The study’s relevance lies in its micro-historical contribution to the historiography of transitional justice in Central Europe. It demonstrates how the Beneš Decrees functioned not only as instruments of accountability but also as instruments of minority policy and post-war state consolidation. By juxtaposing judicial practice with contemporary Catholic episcopal memoranda criticizing collective punishment, the article highlights tensions between ecclesiastical moral discourse and state retribution. As such, the trial of József Király provides an instructive case study for understanding the intersections of minority politics, church–state relations, and legal reckoning in the aftermath of the Second World War.